2023
DOI: 10.1101/2023.03.16.532852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atlas of Fetal Metabolism During Mid-To-Late Gestation and Diabetic Pregnancy

Abstract: Mounting evidence supports an instructive role for metabolism in stem cell fate decisions. However, much is yet unknown about how fetal metabolism changes during mammalian development and how altered maternal metabolism shapes fetal metabolism. Here, we present a descriptive atlas of in vivo fetal murine metabolism during mid-to-late gestation in normal and diabetic pregnancy. Using 13C-glucose and LC-MS, we profiled the metabolism of fetal brains, hearts, livers, and placentas harvested from pregnant dams bet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Maternal/fetal metabolic relationship probed in a recent study revealed that fetal nutrient sourcing was dependent on maternal glycemic state. LCMS and in vivo 13 C-glucose tracing showed sorbitol accumulation in fetal tissues and decreased neurotransmitter levels in the fetal brain isolated from dams with maternal hyperglycemia [ 29 ].…”
Section: Integrative Health and Systemic Disordersmentioning
confidence: 99%
“…Maternal/fetal metabolic relationship probed in a recent study revealed that fetal nutrient sourcing was dependent on maternal glycemic state. LCMS and in vivo 13 C-glucose tracing showed sorbitol accumulation in fetal tissues and decreased neurotransmitter levels in the fetal brain isolated from dams with maternal hyperglycemia [ 29 ].…”
Section: Integrative Health and Systemic Disordersmentioning
confidence: 99%